Inequalities in indicators of early childhood caries experience in the municipality of Andes (Antioquia, Colombia) - Ramírez-Puerta, Blanca Susana; Escobar-Paucar, Gloria; Ochoa-Acosta, Emilia María; Franco-Cortés, Ángela María (Revista Facultad de Odontología Universidad de Antioquia, 2018)
Introduction: identifying inequalities in health is a step towards inequity analysis, a topic that concerns various parties involved in oral health. The aim of the present study was to identify the distribution of indicators of early childhood caries experience. Methods: descriptive study based on data obtained from the baseline study on health indicators in 623 children under six years of age from the municipality of Andes (Antioquia) in 2015. The presence and severity of tooth decay lesions were recorded following the International Caries Detection and Assessment System (ICDAS), calculating the indexes of decayed, filled, and missing teeth due to caries (dICDAS5-dICDAS6 mfs and dICDAS1-6 mfs), as well as Lorenz curves and Gini coefficients for the accumulated frequencies of both indicators. Results: an average dICDAS5-6 mfs of 3.3 ± 7.4 was found as follows: 3.5 ± 8.0 in the rural area and 2.7 ± 5.7 in the urban area. The average dICDAS1-6 mfs was 14.3 ± 15.1, with statistically significant differences by area of residence: 15.7 ± 15.8 in the rural area and 11.3 ± 12.8 in the urban area. The analysis with Lorenz curves showed inequality in distribution of caries experience. The Gini coefficients were 0.412 for dICDAS5-6 mfs and 0.284 for dICDAS1-6 mfs. Conclusion: The analyses show a skewed distribution of dental caries in children under the age of six, and a greater inequality in terms of indicators of dental caries experience in its severe form in the municipality of Andes.